ภาวะผู้นำเชิงเป้าหมาย - และคณะ, พระบุญชู จัตตะมะโล (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2019)
The path goal leadership theory plays on this concept. It is the strategy of leadership that makes the leader’s task to motivate and clarify the group’s goals, essentially making them a coach. This interpretation holds that the leader empowers the group to reach their goals and ensures that they share an awareness of what those goals are. As the leader you are not only charged with giving your team the carrot but making sure that carrot is what they really want (and that they can eventually get it. Path goal leadership theory encourages a strong communication about goals and direction, with a strong relationship between the leader and the group. With a clear set of requirements and providing the tools to complete them, the leader can build a string of successes toward the end target. In achievement-oriented leadership, the leader sets challenging goals for followers, expects them to perform at their highest level, and shows confidence in their ability to succeed. Participative leadership involves leaders consulting with followers and asking for their suggestions before making a decision. It is similar to the democratic leadership style. In supportive leadership, the leader is friendly and approachable. The leader shows concern for the followers’ psychological being, making the team members more comfortable to pursue their own goals. Goal Leadership refers to the goal, by influencing, motivating, trying, and processes based on goodness includes: 1) having goals 2) influencing motivation 3) trying 4) having a process 5) being good.   Keyword: Goal, Leadership